(untitled) (Research, Society and Development, 2019)
The hands of health professionals are the main means of transmission of microorganisms and, therefore, it is necessary to reduce this contamination by hand hygiene. In this perspective, the present study aims to measure the adhesion of the health professionals of the West Metropolitan Hospital Pelópidas Silveira to hand hygiene practices through the WHO Multimodal Strategy and to elaborate a plan of action with the purpose of preventing the transmission of microorganisms and infections related to health care. Research-action observational study. Hand hygiene adherence was identified in 63.7% of the professionals observed, of which, the nursing technicians were the ones who least adhered to this procedure (54.3%), while nurses, doctors and others presented an approximate percentage (71.8% to 79.6%). As for the most used products in the actions of hand hygiene, water and soap obtained 89% of adhesion, followed by alcohol gel with 11%. It is concluded that the adherence of professionals to the practice of hand hygiene was not satisfactory and, therefore, there is a need for continuing education for the team that integrates the service. The plan of action, when implemented, may contribute to the decision making of the next actions carried out by the institution regarding the control of infections related to health care.